2015
DOI: 10.5530/jyp.2015.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Concerning Pharmacogenomics among Pharmacists: A Systematic Review

Abstract: Background: Pharmacists are furnished with expert drug knowledge and have been considered as valuable resource of drug information, therefore, are well positioned to play a leading role in the application of pharmacogenomics (PG) in to clinical practice. This might prevent Chemotherapy related adverse events and improve patient outcomes, despite the ethical, privacy concerns and potential implications of lifelong genetic-data. Methods: This review is to evaluate and digest the various studies on Knowledge, Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 20 publications
9
39
0
Order By: Relevance
“…In contrast, higher knowledge (ranging from 53% to 89%) was reported by prior studies from the USA during the period from 2010 to 2013 [16]. The present findings revealed no significant difference in the level of knowledge among physicians and pharmacists: this is similar to that reported in Qatar [24].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, higher knowledge (ranging from 53% to 89%) was reported by prior studies from the USA during the period from 2010 to 2013 [16]. The present findings revealed no significant difference in the level of knowledge among physicians and pharmacists: this is similar to that reported in Qatar [24].…”
Section: Discussionsupporting
confidence: 73%
“…Most of these studies were conducted in the USA [7,16,1922] and few studies have been performed in Canada, Australia, Europe and Africa [16,23]. Yet, little is known about similar outcomes in the Eastern Mediterranean region: to date, only one study has been published, in Qatar [24].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists in Zimbabwe have limited-to-fair knowledge and awareness of the PGx as highlighted in this study—a scenario not unique to Zimbabwe only or pharmacists but is a global concern across most healthcare professionals as shown by various studies in other LMICs whereby below-average knowledge of PGx was noted [ 14 , 18 , 19 ]. As a result, in Ghana PGx is now taught in some training institutions and as continuing education for doctors and pharmacists [ 14 ].…”
Section: Discussionmentioning
confidence: 87%
“…In the community setting, the internal CPD also may predict the pharmacists' knowledge and the outpatient's service hour could predict pharmacist' attitude. Previous study stated that some characteristics like sex, age, level of education type of service and the intensity of CPD [16][17][18]. Roeder et al showed that pharmacists with Pharm D degree had better knowledge than the lower degree [17].…”
Section: Discussionmentioning
confidence: 99%